Microbial status, aerobic stability and fermentation of maize silage sealed with an oxygen barrier film or standard polyethylene film - Orosz, Szilvia; Wilkinson, John Michael; Wigley, Simon; Bíró, Zsolt; Galló, Judit (Agricultural and Food Science, 2013)
An experiment was conducted to compare a bunker silo sealing system comprising an oxygen barrier film (OB: 45μm thickness) with protective woven polypropylene with one comprising standard black polyethylene film (S; 125μm thickness) with protective tyres. Analysis of samples taken to 30 cm depth after 365 days of storage showed no differences in pH or lactic acid between the two sealing systems. There were no differences in aerobic bacterial count between silages. Whilst 2.56 log10 CFU moulds g-1 fresh weight were found in samples of silage sealed with S, no moulds were found in samples of silage sealed with OB. Aerobic stability, averaged 249 hours and 184 hours for OB and S, respectively. The OB system probably inhibited the development of the micro-organisms responsible for the initiation of aerobic deterioration to a greater extent than the standard silo sealing system.